(untitled) (Global Journal of Management and Business Research, 2013)
The purpose of this study is to investigate important firm-level determinants of capital structure on Ethiopian insurance companies. The study employs panel regression model. The results show that growth, profitability and age of the firm were found to have significant influence on Ethiopian insurance companies’ capital structure. Liquidity and business risk were also significant for long term debt and total debt ratio respectively. However, among the hypothesized capital structure determinants asset tangibility and size of the firm were found to have statistically insignificant contribution on capital structure of Ethiopian insurance companies.